Adoption and implementation of IoT technology for hybrid renewable energy system - Ismail F.B.; Dihrab S.; Al-Bazi A.; Azahar N.A.H. (American Institute of Physics, 2025)
The Internet of Things (IoT) in the renewable energy sector is a communication network that connects the sensors in different renewable energy resources and the software for exchanging data or carrying out functions. Continuous monitoring, forecasting of electric energy usage, and renewable energy power generation are needed for optimal power use and consumption. New networking and data processing tools are being used in projects to promote the integration of renewable energies and leverage their resources. This study shows the result of using IoT to monitor hybrid renewable systems for stand-alone in rural areas. This study aims to implement and adopt a better and more efficient wireless monitoring system to access information and create an automated workflow. Solutions based on IoT protocol allow remote monitoring and optimizing power management. The system consists of a solar panel, charge controller, battery, inverter, load, and IOT system to monitor its electrical parameters. The result of the study shows that the system has high accuracy with 98.6%. ? 2024 Author(s).